Analysis of farmers' communication network and factors of knowledge regarding agro meteorological parameters - KUMAR, K RAVI; NAIN, M S; SINGH, RASHMI; CHAHAL, V P; BANA, R S (The Indian Journal of Agricultural Sciences, 2015)
Understanding communication networks bear significant importance for undertaking interventions regarding local information needs. It becomes more important if the issues of sensitivity like climate change and its effect on agriculture has to be dealt. The agricultural sector needs accurate, reliable and timely weather and climate information for daily tactical decisions and long-term planning for crop management. They can potentially alter selection and management of crops based on new information obtained within a few weeks or days of planting. The information systems integrating agricultural educators, researchers, extensionists and farmers need to be introduced for agriculture sector for which sufficient data base regarding the gap between the possessed knowledge and the available knowledge and the information source utilization pattern need to be generated. The present study to find out the factors of the knowledge of farmers regarding climate and weather in relation to crop management and the analysis of farmers' communication network was undertaken in Adilabad district (highly vulnerable to climate change effects) of Telangana state of India. A knowledge test specifically designed was administered to 120 respondents and was found that majority of the respondents had moderate level of knowledge. The socio-economic and psycho-personal variables like education, occupation, family type, land holding, social participation, economic motivation, innovativeness, scientific orientation and risk orientation showed positive and significant relationship with knowledge level and in regression analysis education, scientific orientation were positive and had significant contribution to the knowledge level of respondents. Television, radio, agriculture officer and progressive farmers were categorized into strong group of information sources usefulness. In order to support farm level decisions and minimize the loses in adverse climatic and weather conditions farmers' understanding about interaction of climate and agro-ecosystem need to be bridged through inclusion of farmers' communication network